2013
DOI: 10.1186/ar4304
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of synovitis in patients with rheumatoid arthritis using fluorescence optical imaging

Abstract: IntroductionTo prospectively evaluate quantitative assessment of fluorescence optical imaging (FOI) for differentiation of synovitic from non-synovitic joints in patients suffering from rheumatoid arthritis (RA).MethodsFOI of the hands was performed in patients with active RA, and a stratified quantitative fluorescence readout (FLRO) of 3 phases (1-120 s; 121-240 s; 241-360 s) was generated for 5 individual joints of the clinical predominant hand (carpal joint, metacarpophalangeal and proximal interphalangeal … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 35 publications
1
33
1
2
Order By: Relevance
“…Indeed, early enhancement of contrast agents is currently widely discussed as an important marker for synovial vascularity in the context of MRI studies 38,39,40,41 . On the other hand, Schafer, et al found best results for intermediate (P2) and late enhancement (P3), applying dynamic raw data analysis, although their definition of phases substantially differs from this present study, because phases are defined by time only (P1: 0-120 s; P2: 120-240 s, P3: 240-360 s) 23 .…”
Section: Rheumatologycontrasting
confidence: 79%
See 3 more Smart Citations
“…Indeed, early enhancement of contrast agents is currently widely discussed as an important marker for synovial vascularity in the context of MRI studies 38,39,40,41 . On the other hand, Schafer, et al found best results for intermediate (P2) and late enhancement (P3), applying dynamic raw data analysis, although their definition of phases substantially differs from this present study, because phases are defined by time only (P1: 0-120 s; P2: 120-240 s, P3: 240-360 s) 23 .…”
Section: Rheumatologycontrasting
confidence: 79%
“…FOI with IV administration of nonspecific fluorophores, such as ICG, depicts disturbances of microvascularization of the examined area. In studies with animal models, FOI has shown to be an appropriate imaging method for the detection of arthritis 18,19 ; however, only a few in vivo studies have been conducted in humans to evaluate FOI as a diagnostic approach in arthritides 11,13,14,15,17,22,23 . MRI and US are capable of depicting inflammatory thickening and hypervascularization of the synovial membrane in RA, which is suspected of leading to bone and joint destruction in the course of disease 17,32,33,34,35,36,37 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since hypoxia affects both tissue blood content and oxygenation [22,24], near-infrared optical methods-diffuse optical spectroscopy (DOS) and tomography (DOT), and photoacoustic tomography (PAT)-that are sensitive to these physiological parameters are being developed to supplement/replace clinical assessment and radiology for RA monitoring [25][26][27][28][29][30][31][32][33][34]. These emerging techniques, DOS in particular, have the potential to overcome most of the limitations of current RA monitoring methods since they are safe, relatively inexpensive, and have the potential to quickly and objectively assess RA inflammation at the individual joint level [34,35].…”
Section: Introductionmentioning
confidence: 99%